Peroxiredoxin 6 from the Antarctic emerald rockcod: molecular characterization of its response to warming - TOLOMEO, ANNA MARIA; CARRARO, ANDREA; BAKIU, RIGERS; TOPPO, STEFANO; FERRO, DIANA; SANTOVITO, GIANFRANCO; Place, S. P (Journal of Comparative Physiology B, 2016)
In the present study, we describe the purification and molecular characterization of two peroxiredoxins (Prdxs), referred to as Prdx6A and Prdx6B, from Trematomus bernacchii, a teleost widely distributed in many areas of Antarctica, that plays a pivotal role in the Antarctic food chain. The two putative amino acid sequences were compared with Prdx6 orthologs from other fish, highlighting a high percentage of identity and similarity with the respective variant, in particular for the residues that are essential for the characteristic peroxidase and phospholipase activities of these enzymes. Phylogenetic analyses suggest the appearance of the two prdx6 genes through a duplication event before the speciation that led to the differentiation of fish families and that the evolution of the two gene variants seems to proceed together with the evolution of fish orders and families. The temporal expression of Prdx6 mRNA in response to short-term thermal stress showed a general upregulation of prdx6b and inhibition of prdx6a, suggesting that the latter is the variant most affected by temperature increase. The variations of mRNA accumulation are more conspicuous in heart than the liver, probably related to behavioral changes of the specimens in response to elevated temperature. These data, together with the peculiar differences between the molecular structures of the two Prdx6s in T. bernacchii as well as in the tropical species Stegastes partitus, suggest an adaptation that allowed these poikilothermic aquatic vertebrates to colonize very different environments, characterized by different temperature ranges.